Interactive SVBRDF Modeling from a Single Image - Dong, Yue; Lin, Steve; Guo, Baining (Material Appearance Modeling: A Data-Coherent Approach, 2013)
In this chapter, an interactive system called AppGen is presented for modeling material appearance from a single example image. Given a texture image of a nearly planar surface lit with directional lighting, this system models the detailed spatially-varying reflectance properties and surface normal variations with minimal user interaction. Users are asked to provide simple shading and reflectance information via a few roughly marked strokes on the image, and the system uses this information together with some image analysis to assign reflectance properties and surface normals to each pixel. This system generates convincing results within minutes of interaction and works well for a variety of material types that exhibit different reflectance and normal variations, including natural and man-made surfaces.